INFORMATICS TERMINOLOGY: BETWEEN INCOMPLETENESS AND REDUNDANCY - Mintii Ірина; Stetsyshyna Олександра; Tarasova Олена; Vakaliuk Тетяна; Semerikov Сергій (Journal of Information Technologies in Education (ITE), 2024)
The article addresses the problem of forming informatics terminology in the process of teaching primary school pupils. The relevance of the research is driven by the introduction of informatics as a compulsory subject from year 2 in accordance with the State Standard of Primary Education in Ukraine. Different approaches to structuring the content of informatics education, implemented in model educational programmes under the guidance of O. Ya. Savchenko and R. B. Shyian, as well as the authors’ methodological systems of school textbook compilers, may cause discrepancies in the interpretation and use of informatics terms. Incorrect or inconsistent use of terminology on the pages of textbooks and in teachers’ speech can lead to pupils’ misconceptions and hinder the formation of informatics competencies. A comparative analysis of the terminology of model educational programmes in informatics for years 1-4 revealed certain differences between the terminological apparatus of the programmes under the guidance of O. Ya. Savchenko and R. B. Shyian. The two programmes share 15 terms, including «information», «message», «data», «information processes», «algorithm», «executor», and others. At the same time, each programme contains a number of unique terms not mentioned in the other. Based on a comparative analysis of the terminological apparatus of 9 informatics textbooks for year 4, recommended by the Ministry of Education and Science of Ukraine, the level of their terminological completeness and redundancy in relation to the relevant educational programmes was determined. It was found that the textbooks by N. V. Morze and O. V. Barna (according to the programme of O. Ya. Savchenko) and H. V. Lomakovska and H. O. Protsenko (according to the programme of R. B. Shyian) are the most terminologically consistent with the programmes. The textbooks by T. H. Hilberg et al. and O. V. Korshunova were found to be the least consistent with the programmes in terms of terminological content. It is concluded that there is a need for careful alignment of textbook terminology with the relevant educational programmes.